Relationship Between Mentor Retention and the Role of Personality: A Descriptive-Analytical Study - Maghbouli N; Khabaz Mafinejad M; Pourhassan S (Journal of Multidisciplinary Healthcare, 2020)
Nastaran Maghbouli,1,2 Mahboobeh Khabaz Mafinejad,3 Saeed Pourhassan4 1Department of Physical Medicine and Rehabilitation, School of Medicine, Tehran University of Medical Sciences, Tehran, Iran; 2Mentoring Office, Faculty Education Deputy, School of Medicine, Tehran University of Medical Sciences, Tehran, Iran; 3Department of Medical Education, Education Development Center (EDC), Health Professions Education Research Center, Tehran University of Medical Sciences, Tehran, Iran; 4Department of Internal Medicine, Shariati Hospital, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Saeed PourhassanDepartment of Internal Medicine, Shariati Hospital, Tehran University of Medical Sciences, Tehran, IranEmail Saeed.Pourhassan@gmail.comPurpose: According to the nature of mentoring, losing mentors reduces a program’s capacity and causes a waste of resources to recruit, screen, and train new mentors. The purpose of this study was to assess the relationship between personality traits and retention intention among mentors and also the duration of mentor retention.Methods: This is a descriptive-analytical study conducted at Tehran University of Medical Sciences. To assess relationship of mentor retention with their personality traits, one hundred forty mentors were surveyed. Participants were surveyed using the Temperament and Character Inventory. We used independent t-test, Pearson correlation and regression analysis with SPSS version 20.Results: The response rate was 70%; of 98 respondents, 30.6% were male. There was a significant mean difference for self-transcendence and self-directedness traits with the mentors’ intention to retention, respectively (t= 1.672, p =0.046 and t= 2.761, p =0.011). Furthermore, novelty seeking and self-directedness traits significantly predicted the mentor’s intention to retention [OR=5.583 (1.656– 18.826), 5.284 (1.310– 21.309); respectively].Conclusion: According to findings, the improved mentor’s attitudes to retain in program may, therefore, be explained by an increase in mentors’ self-directedness and novelty-seeking traits. Policy maker and educational managers should renew the process of recruitment of mentors and introduce supportive strategies every year to retain mentors, which can contribute to their retention.Keywords: traits, mentoring, personality, retention, temperament